A silicon photoanode for efficient ethanol oxidation under alkaline conditions. Issue 35 (19th April 2017) - Cai, Qian; Hong, Wenting; Li, Jing; Jian, Chuanyong; Liu, Wei
Abstract : A Pt/ZrO2 /n-Si electrode has been employed as the anode for the EOR, exhibiting improved EOR activity and durability under solar illumination. Abstract : Silicon (Si) is an attractive semiconductor which has broad applications in photovoltaic fields due to its low cost and narrow band gap (∼1.1 eV). Taking advantage of a Si-based metal–insulator–semiconductor (MIS) device, which has high electron–hole separation efficiency due to the confined electron and hole transport directions, for the first time, a Pt/ZrO2 /n-Si photoanode is directly employed as the anode for the ethanol oxidation reaction (EOR). When exposed to visible light irradiation, the Pt/ZrO2 /n-Si photoanode exhibits apparently improved EOR activity and durability. This work provides a simple way to fabricate Si-based EOR photoanodes, which has potential for application in direct ethanol fuel cells.